2018
DOI: 10.3389/fpls.2018.00536
|View full text |Cite
|
Sign up to set email alerts
|

Higher Temperature at Lower Elevation Sites Fails to Promote Acclimation or Adaptation to Heat Stress During Pollen Germination

Abstract: High temperatures associated with climate change are expected to be detrimental for aspects of plant reproduction, such as pollen viability. We hypothesized that (1) higher peak temperatures predicted with climate change would have a minimal effect on pollen viability, while high temperatures during pollen germination would negatively affect pollen viability, (2) high temperatures during pollen dispersal would facilitate acclimation to high temperatures during pollen germination, and (3) pollen from population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 83 publications
2
18
0
Order By: Relevance
“…Our findings that male reproduction was negatively affected by drought supports other research documenting the potential sensitivity of pinyon pine reproduction to climate change. Cone production has declined broadly across the landscape (Redmond et al, 2012) and pollen germination is impaired by the temperatures that P. edulis is predicted to experience as climate changes (Flores-Renteria et al, 2018). In this long-term study, we also saw declines in the production of male strobili with drought.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings that male reproduction was negatively affected by drought supports other research documenting the potential sensitivity of pinyon pine reproduction to climate change. Cone production has declined broadly across the landscape (Redmond et al, 2012) and pollen germination is impaired by the temperatures that P. edulis is predicted to experience as climate changes (Flores-Renteria et al, 2018). In this long-term study, we also saw declines in the production of male strobili with drought.…”
Section: Discussionmentioning
confidence: 99%
“…Our data indicate that drought is likely to increase this difference; declining strobili production following drought suggest that resistant trees are even less likely to serve as pollen donors under drought. Research on pollen viability conducted on cinder soils showed that P. edulis pollen was highly sensitive to the temperatures predicted with climate change during both the dispersal and germination stages of development (Flores-Renteria et al, 2018). Further research is necessary to determine if resistant and susceptible trees now differ in pollen viability, potentially further shifting male function to moth susceptible, drought tolerant trees.…”
Section: Discussionmentioning
confidence: 99%
“…Various sorghum genotypes show in vitro pollen germination reductions of 2-95 % under different heat stresses (Sunoj et al, 2017). In vivo experiments with pollen from rice or the pine Pinus edulis gave similar results (Flores-Rentería et al, 2018;Shi et al, 2018).…”
Section: Introductionmentioning
confidence: 86%
“…Tree life history stages from reproduction through seedling establishment are vulnerable to abiotic stress related to climate warming [ 13 ]. High temperatures and drought can limit seed production [ 2 , 14 ] and seedling establishment [ 15 ]. Temperature affects the production and quality of tree seeds in forests ranging from dry temperate [ 14 ] to subarctic regions [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…High temperatures and drought can limit seed production [ 2 , 14 ] and seedling establishment [ 15 ]. Temperature affects the production and quality of tree seeds in forests ranging from dry temperate [ 14 ] to subarctic regions [ 16 ]. Longer periods of seed development (e.g.…”
Section: Introductionmentioning
confidence: 99%